Estimating the Effects of Credit Constraints on Productivity of Peruvian Agriculture - Woutersen, Tiemen; Khandker, Shahidur R. (World Bank, Washington, DC, 2014)
This paper proposes an estimator for the endogenous switching regression models with fixed effects. The estimator allows for endogenous selection and for conditional heteroscedasticity in the outcome equation. Applying the estimator to a dataset on the productivity in agriculture substantially changes the conclusions compared to earlier analysis of the same dataset. This paper proposes an estimator for the endogenous switching re-gression models with fixed effects. The estimator allows for endogenous selection and for conditional heteroscedasticity in the outcome equation. Applying the estimator to a dataset on the productivity in agriculture substantially changes the conclusions compared to earlier analysis of the same dataset.